Agribisnis Pengembangan Plasma Nutfah Kabupaten Lumajang Provinsi Jawa Timur: Studi Komoditas Pisang Mas Kirana - Suwandari, Anik; Puspaningrum, Diah; Soejono, Djoko; Zahrosa, Dimas Bastara; Maharani, Ariq Dewi; Prabowo, Rachmat Udhi; Amam, Amam (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Mas Kirana’s banana is a germplasm as well as an icon of Lumajang District, East Java Province. Mas Kirana bananas are designated as Indonesian genetic resources based on the Decree of the Minister of Agriculture of the Republic of Indonesia Number 516/Kpts/SR.120/12/2005. This study aims to formulate a pattern of business capital formation and development strategy for Mas Kirana banana commodity as an effort to preserve Indonesia's germplasm. Data collection was done by structured interview method. Determination of the sample is done by snowball sampling technique. Data analysis was carried out using qualitative descriptive methods and Force Field Analysis (FFA). The results showed that the pattern of capital business capital formation for Mas Kirana's banana consisted of family capital, financial institution capital, non-financial institutional capital, and personal capital. The identification process resulted in 7 (seven) driving factors and 7 (seven) inhibiting factors for Mas Kirana banana development. Key Success Factors (FKK) for developing Mas Kirana Banana Farmers Groups on the driving factor dimension are the Mas Kirana Banana commodity which has a comparative advantage and is certified Geographically Indication (GI), while the inhibiting factor dimension is the weakness of farmer resources in managing and developing group finances. Based on the FKK value of the driving and inhibiting factors, the recommended strategy is farmer institutional engineering through the formation of the Mas Kirana banana farmer cooperative.